A framework for identifying and characterising coral reef "oases" against a backdrop of degradation. Issue 6 (18th June 2018) - Guest, James R.; Edmunds, Peter J.; Gates, Ruth D.; Kuffner, Ilsa B.; Andersson, Andreas J.; Barnes, Brian B.; Chollett, Iliana; Courtney, Travis A.; Elahi, Robin; Gross, Kevin; Lenz, Elizabeth A.; Mitarai, Satoshi; et al.
Abstract: Human activities have led to widespread ecological decline; however, the severity of degradation is spatially heterogeneous due to some locations resisting, escaping, or rebounding from disturbances. We developed a framework for identifying oases within coral reef regions using long‐term monitoring data. We calculated standardised estimates of coral cover ( z ‐scores) to distinguish sites that deviated positively from regional means. We also used the coefficient of variation (CV) of coral cover to quantify how oases varied temporally, and to distinguish among types of oases. We estimated "coral calcification capacity" (CCC), a measure of the coral community's ability to produce calcium carbonate structures and tested for an association between this metric and z ‐scores of coral cover. We illustrated our z ‐score approach within a modelling framework by extracting z ‐scores and CVs from simulated data based on four generalized trajectories of coral cover. We then applied the approach to time‐series data from long‐term reef monitoring programmes in four focal regions in the Pacific (the main Hawaiian Islands and Mo'orea, French Polynesia) and western Atlantic (the Florida Keys and St. John, US Virgin Islands). Among the 123 sites analysed, 38 had positive z ‐scores for median coral cover and were categorised as oases. Synthesis and applications . Our framework provides ecosystem managers with a valuable tool for conservation by identifying "oases" within degraded areas. By evaluating trajectories of change in state (e.g., coral cover) among oases, our approach may help in identifying the mechanisms responsible for spatial variability in ecosystem condition. Increased mechanistic understanding can guide whether management of a particular location should emphasise protection, mitigation or restoration. Analysis of the empirical data suggest that the majority of our coral reef oases originated by either escaping or resisting disturbances, although some sites showed a high capacity for recovery, while others were candidates for restoration. Finally, our measure of reef condition (i.e., median z ‐scores of coral cover) correlated positively with coral calcification capacity suggesting that our approach identified oases that are also exceptional for one critical component of ecological function. Abstract : Our framework provides ecosystem managers with a valuable tool for conservation by identifying "oases" within degraded areas. By evaluating trajectories of change in state (e.g., coral cover) among oases, our approach may help in identifying the mechanisms responsible for spatial variability in ecosystem condition. Increased mechanistic understanding can guide whether management of a particular location should emphasise protection, mitigation or restoration. Analysis of the empirical data suggest that the majority of our coral reef oases originated by either escaping or resisting disturbances, although some sites showed a high capacity for recovery, while others were candidates for restoration. Finally, our measure of reef condition (i.e., median z ‐scores of coral cover) correlated positively with coral calcification capacity suggesting that our approach identified oases that are also exceptional for one critical component of ecological function.